2022
DOI: 10.1021/acsami.2c01312
|View full text |Cite
|
Sign up to set email alerts
|

Nontraditional Aldol Condensation Performance of Highly Efficient and Reusable Cs+ Single Sites in β-Zeolite Channels

Abstract: Aldol reactions (self- and cross-aldol condensations) for conjugated enone synthesis were efficiently performed on large-sized Cs+ single sites (1 wt %) confined in β-zeolite channels in toluene, which showed the highest level of catalytic aldol condensation activity among reported zeolite catalysts. In general, aldol condensation reactions for C–C bond synthesis can proceed by acids (e.g., H+), bases (e.g., OH–), enolate species, and acidic or basic solid catalysts. However, the Cs+ single site/β sample witho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…The number of experimental reports on Pt SACs has increased exponentially in the last years. A growing number of literature works report on the synthetic strategies, spectroscopic characterization, and reactivity of isolated Pt catalysts for a large number of applications. An inspection to these works indicates that the unambiguous identification of isolated Pt sites is one of the greatest challenges. In particular, distinguishing the IR absorption bands of CO when it is adsorbed on isolated Pt sites, oxidized Pt clusters (hereafter Pt iso and Pt ox , adopting the nomenclature of Cristopher and co-workers) or subnanometric Pt clusters is not straightforward.…”
Section: Ductility Of Pt-based Catalysts In the Presence Of (Reactive...mentioning
confidence: 99%
“…The number of experimental reports on Pt SACs has increased exponentially in the last years. A growing number of literature works report on the synthetic strategies, spectroscopic characterization, and reactivity of isolated Pt catalysts for a large number of applications. An inspection to these works indicates that the unambiguous identification of isolated Pt sites is one of the greatest challenges. In particular, distinguishing the IR absorption bands of CO when it is adsorbed on isolated Pt sites, oxidized Pt clusters (hereafter Pt iso and Pt ox , adopting the nomenclature of Cristopher and co-workers) or subnanometric Pt clusters is not straightforward.…”
Section: Ductility Of Pt-based Catalysts In the Presence Of (Reactive...mentioning
confidence: 99%
“…Zeolites are among the most functional heterogeneous catalysts with high surface areas and uniformly nano-sized pores for molecular diffusion. [19][20][21][22][23][24][25][26][27][28][29][30][31][32] Aluminosilicates are the main crystalline components in the zeolite framework, showing high thermal stability. The acidity and basicity attributed to the aluminosilicate are known to function as active sites in acid/base reactions, and some zeolites have been reported to exhibit catalytic activity for C-C coupling based on the aldol reaction.…”
Section: Introductionmentioning
confidence: 99%
“…2,10,23 Ghosh et al also discovered that the Cs + single sites located within channels of β zeolite through ion exchange showed highly efficient catalytic activity for the self-and cross-aldol condensation and that the active centers were proposed to be monovalent Cs + single sites. 24 Supported Cs catalysts are expected as promising candidates; however, active centers of aldol condensation still need in-depth investigation.…”
Section: ■ Introductionmentioning
confidence: 99%
“…For the optimized catalyst of 20% VPO-TiO 2 , the acetic acid conversion and (AA+MA) selectivity achieved 29–31 and 85%, respectively . Noteworthily, VPO catalysts are involved more than surface acid–base-catalyzed aldol condensation, which is also applied to the complex oxidation–reduction because of the complicated crystalline phase and structure, resulting in the formation of byproducts and rapid deactivation of catalysts. , Many studies on aldol condensation of MA with FA have been conducted over Cs catalysts supported on Al 2 O 3 , SiO 2 , and SBA-15 via simple impregnation methods with excellent catalytic performance. Previous research studies have reported that the Si–O–Cs active sites through the interaction of Cs + with Si–OH groups were proposed as active centers to promote the dispersion of Cs species and catalytic performance. ,, Ghosh et al also discovered that the Cs + single sites located within channels of β zeolite through ion exchange showed highly efficient catalytic activity for the self- and cross-aldol condensation and that the active centers were proposed to be monovalent Cs + single sites . Supported Cs catalysts are expected as promising candidates; however, active centers of aldol condensation still need in-depth investigation.…”
Section: Introductionmentioning
confidence: 99%